Analisis Penerapan Jaminan pada Pembiayaan Mudharabah dan Musyarakah di Perbankan Syariah - Astriah; Muhammad Kamal Zubair (Institut Agama Islam Negeri Parepare, 2021)
Sharia Banking is a financial institution that has sharia principles and applies Islamic law in making decisions. In the form of disbursement of funds that can be accessed by using mudharabah and musyarakah financing, the concept of mudharabah and musyarakah has the principle of trust (trust) but in practice Islamic banks apply guarantees in their financing, this is not in accordance with the initial principle of mudharabah and musyarakah, namely the trust system. The purpose of this study is to determine the difference between mudaraba and musyarakah in Islamic banking and to determine the application of existing guarantees in Islamic banking. This type of research uses a library research approach. The primary data source is the book